Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/su12020500
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the Sustainable Development Goals from an Ecosystem Conducive to the SE: The Galician’s Case

Abstract: The special alignment of the principles and effects of the social economy (SE) with the Sustainable Development Goals (SDGs) renders this area especially suitable for the implementation of the 2030 Agenda and the achievement of these goals, favoring a paradigm shift towards a new economic system that reconciles growth and sustainability. In this context, governments and institutions can moderate or accelerate this path, with the implementation of a series of policies to promote and drive the social economy. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
0
16
0
7
Order By: Relevance
“…In recent years, cooperatives have noticeably expanded where, surprisingly, many other businesses collapsed during the worst period of the financial crisis [3]. In addition, an increasing number of women are engaging in cooperatives, to the extent that the percentage of women in the workforce of these organizations surpasses by far that of women in the workforce as a whole [4,5]. This issue has grown in importance considering previous research showing that business entrepreneurs are twice as likely to be male, while numbers of male and female social entrepreneurs were similar [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cooperatives have noticeably expanded where, surprisingly, many other businesses collapsed during the worst period of the financial crisis [3]. In addition, an increasing number of women are engaging in cooperatives, to the extent that the percentage of women in the workforce of these organizations surpasses by far that of women in the workforce as a whole [4,5]. This issue has grown in importance considering previous research showing that business entrepreneurs are twice as likely to be male, while numbers of male and female social entrepreneurs were similar [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with many other studies: (i) in the first international conference on SDGs and SSE, held in Geneva in 2019 and sponsored by UNRISD, SDGs 5, 8, and 12 appeared as the most concurrent among experiences from around the world [9]; (ii) a research study among social enterprises in Spain also showed that the SDGs to which they thought they contributed most were numbers 8, 4, 5, and 12 [24]; (iii) at the local level as well, Bastida et al [14], in this issue of Sustainability, present SDGs 5, 8 as the more common.…”
Section: Discussionmentioning
confidence: 99%
“…This often happens in local territorialized contexts, since location and geographical and cultural embeddedness is one typical characteristic of many of these experiences. In that sense, they can have a better awareness of environmental sustainability issues because they live in the very same territory and are directly affected [14].…”
Section: Linking the Sse And Sdgsmentioning
confidence: 99%
See 2 more Smart Citations